Propuesta de buenas prácticas ambientales sostenibles para el Hotel Libertador de la Ciudad de Loja - Quishpe Salas., María Esther (2023)
There is a lack of knowledge about the application of good environmental practices (GEP) in the service sector, the present research is proposed for hotels; general objective, to propose good environmental practices for the Libertador hotel, to know to what extent these are applied and if they are done correctly, two specific objectives are derived from this objective, to carry out a diagnosis of good environmental practices of resources, water, energy and solid waste and to design a GEP manual. For the first objective, the mixed method was used, a diagnosis of the GEP of the aforementioned resources was made, the performance criteria of the Consejo Global del Turismo Sostenible were used, matrices of the Ministerio de Turismo (MINTUR), to know the consumption of resources, an interview was applied to the manager to know the state of GEP, surveys were applied to the guests to determine their opinions regarding the environmental performance criteria, an evaluation matrix was used to measure the level of sustainability of the hotel. For the second objective, the data from objective one was used to design the proposal, using the Rainforest Alliance sustainable tourism best practices manual as a reference. As a final result, the performance of the resources was evaluated using a matrix, measuring the level of compliance and valuation of the three resources, obtaining a level of sustainability that was insufficient, with a degree of performance that requires total intervention and reformulation for better operation, It was also determined that the water resource, with a weighted score of (0.748), energy (0.684) and solid waste (0.312), the three resources have a low performance in environmental practices, in conclusion, the manual of good sustainable practices for the Hotel is an instrument that aims to guide and raise awareness among employees and customers about BPAS.